2010
DOI: 10.1021/ie100389v
|View full text |Cite
|
Sign up to set email alerts
|

Novel pH-Sensitive Hydrogels Prepared from the Blends of Poly(vinyl alcohol) with Acrylic Acid-graft-Guar Gum Matrixes for Isoniazid Delivery

Abstract: A novel type of pH-sensitive hydrogel blend of poly(vinyl alcohol) with acrylic acid-graft-guar gum has been prepared. Microspheres with a size of ∼10 µm were produced by the water-in-oil (w/o) emulsification method for investigating the controlled release of an antituberculosis drug, isoniazid. These novel carriers were analyzed for surface morphology, size, effect of pH, swelling, drug loading, and in vitro release of isoniazid in pH 1.2 and 7.4 media. The kinetics of drug release was analyzed using empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(43 citation statements)
references
References 27 publications
(35 reference statements)
2
41
0
Order By: Relevance
“…However, no such intense crystallographic peaks of the drug were found in the spectrum of fresh and aged beads ( Figure 6C and D) and only peaks of pacebo beads with amorphous character were seen ( Figure 6E). The thermal and X-ray crystallographic data supported each other strongly and thus confirming the molecular or amorphous dispersion of drug in the HPAmGG hydrogel beads during preparation and even after stability study at accelerated storage conditions of temperature and humidity (Nath et al, 2010) and the absence of crystals in drug-loaded formulations (Sullad et al, 2010). With reference to drug-polymer systems, the formation and stability of the amorphous form may be primarily due to drug and polymer hydrogen bonding interactions, viscosity of polymer, and glass transition temperature of the mixture (Choksi et al, 2008).…”
Section: Drug-polymer Compatibilitysupporting
confidence: 68%
“…However, no such intense crystallographic peaks of the drug were found in the spectrum of fresh and aged beads ( Figure 6C and D) and only peaks of pacebo beads with amorphous character were seen ( Figure 6E). The thermal and X-ray crystallographic data supported each other strongly and thus confirming the molecular or amorphous dispersion of drug in the HPAmGG hydrogel beads during preparation and even after stability study at accelerated storage conditions of temperature and humidity (Nath et al, 2010) and the absence of crystals in drug-loaded formulations (Sullad et al, 2010). With reference to drug-polymer systems, the formation and stability of the amorphous form may be primarily due to drug and polymer hydrogen bonding interactions, viscosity of polymer, and glass transition temperature of the mixture (Choksi et al, 2008).…”
Section: Drug-polymer Compatibilitysupporting
confidence: 68%
“… M t is the amount of drug released at time t ; M ∞ is the amount of drug released at infinite time; Q is the amount of drug remaining at time t ; Q 0 is the amount of drug remaining at t = 0; k , K 0 , K 1 , K H , and K C are the release constants obtained from the linear curves of Korsmeyer–Peppas, zero‐order, first‐order, Higuchi, and Hixson–Crowell cube root equations, respectively. 34 …”
Section: Resultsmentioning
confidence: 99%
“…From the literature, it has been observed that various graft copolymers of guar gum have been synthesized by grafting with different monomers for instance acrylamide [19], acrylic acid [23], acrylamido glycolicacid [24], acrylonitrile [25], N-vinyl pyrrolidone [26], methacrylamide [27], etc.…”
Section: Introductionmentioning
confidence: 99%